States of exception, human rights, and social harm: Towards a border zemiology - Soliman, Francesca (Theoretical criminology, 2021)
Crimmigration, that is, the merging of criminal and migration law, is receiving increasing attention within criminology. However, while crimmigration widens our understanding of coercion and punishment, it is a reductive lens through which to make sense of migration control. This article comprises three parts: first, I critique the concept of crimmigration, its conceptual foundations, and its methodological limitations. Second, I explore how migration control practice transcends both the state’s territory and sovereignty, using the example of the European Union’s policy of non-assistance, and argue that this policy evidences the need to move beyond crime-based categories in favour of a social harm-based approach. Lastly, I propose a zemiological methodology for the study of migration control, based on a critical realist view of society and building on Nancy Fraser’s idea of social justice. The resulting framework provides a coherent and empirically useful tool for the study of border-related harms.